Energy-efficient processing in radio astronomy: comparative analysis of computing platforms and their implementation - Schuster, Nikola (Stellenbosch : Stellenbosch University, 2025)
Schuster, N. 2025. Energy-Efficient Processing in Radio Astronomy: Comparative Analysis of Computing Platforms and their Implementation. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/bf939b00-9e5b-4fd2-ad7e-22c73f381666